Function of The Language Style Used in Women Commercial Product Advertisements: A Stylistic Analysis of Language - Ginting, Sinta P Amelia; Rangkuti, Rahmadsyah; Yusuf, Muhammad (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2020)
The objectives of this research are to find out the types of the language style used in selected Woman Commercial Product Advertisement and to explain the function of language style in selected Woman Commercial Product Advertisement. The concept of stylistic is analyzed by using William Wells’s theory which discussed about language style. A qualitative research method is used in analyzing this research. The result of this research shows that some types of language style are found in the data. From 10 advertisements analyzed, the researcher found 4 hard cell styles, 3 soft cell styles, 2 slice of life styles, and 1 demonstration style. Hard cell style mostly appears in women product’s advertisements because the advertiser mostly used a rational informational message that is designed to touch the mind and to create a response based on logic.